AB1376 Adherence to subcutaneous vs. oral disease-modifying antirheumatic drugs in rheumatoid arthritis. (23rd January 2014) - Bergman, M.; Bao, Y.; Ayyagari, R.; Mulani, P.M.
Abstract : Background: Adherence to chronic medication regimens in rheumatoid arthritis (RA) can impact drug effectiveness and prevent disease progression and disability. Drug adherence in RA could be impacted by efficacy, tolerability, and mode of administration. Objectives: To assess the association between oral administration (once or twice daily) vs. subcutaneous (SC) injection (weekly or every other week) on drug adherence in RA following achievement of a stable dose. Methods: Patients with at least 2 diagnoses of RA who newly added oral or SC injectable disease-modifying antirheumatic drugs (DMARDs) to oral methotrexate were identified from medical claims data in the Thomson Reuters MarketScan® database (2000–2010). To control for the impact of initial efficacy and tolerability of the added DMARD on adherence, patients were required to achieve a stabilized dose of the added DMARD, defined as a refill at the same dose as the previous fill and occurring ≥90 days after the initial fill. The first refill meeting the criteria was taken as the index date. Patients adding infrequently used DMARDs (<100 patients) or DMARDs not recommended by ACR guidelines were excluded. Adherence was defined as having prescriptions for the added DMARD covering >80% of the 6 months after the index date. Rates of adherence in patients receiving oral or SC injectable DMARDs were compared using multivariate logistic regressions with adjustment for age, sex, employment status, the Charlson comorbidity index, total pill burden, medical resource use (ie, inpatient, emergency department, and outpatient), medical service costs, drug efficacy, oral and SC injectable steroid use, and dosage adjustments of other DMARDs or steroids in the baseline period. Results: A total of 62, 063 patients were identified as initiating a new oral or SC injectable DMARD in combination with oral methotrexate. Among these, 7084 achieved stable doses: 3087 (43.5%) in the oral group including leflunomide (n=632, 8.9%), hydroxychloroquine (n=2041, 28.8%), and sulfasalazine (n=414, 5.8%) and 3997 (56.4%) in the SC injection group (adalimumab or etanercept). Before adjustment, the adherence rate in the SC injection group was 71.1% compared with 65.2% for the oral DMARD group (in particular, 66.1% for leflunomide, 66.7% for hydroxychloroquine, and 56.3% for sulfasalazine). After adjustment for baseline characteristics, patients who added SC injections were significantly more likely to be adherent compared with those adding oral DMARDs (odds ratio [OR]=1.31, 95% confidence interval [CI]=1.19–1.46, P <.001). In particular, patients who added SC injections were significantly more likely to be adherent than those adding leflunomide (OR=1.28, 95% CI=1.07–1.54, P <.001), hydroxychloroquine (OR=1.21, 95% CI=1.08–1.36, P =.007) or sulfasalazine (OR=1.96, 95% CI=1.59–2.41, P <.001). Conclusions: Among patients with RA achieving a stable dose after at least 90 days on a new DMARD, those adding a SC injectable DMARD to oral methotrexate had significantly better adherence than those adding an oral DMARD, after adjusting for efficacy, tolerability and disease severity proxies available in the medical claims data. Disclosure of Interest: M. Bergman Grant/Research support from: Abbott, Consultant for: Abbott, Speakers Bureau: Abbott, Y. Bao Shareholder of: Abbott, Employee of: Abbott, R. Ayyagari Consultant for: Abbott (Analysis Group is under contract with Abbott), Employee of: Analysis Group, P. Mulani Shareholder of: Abbott, Employee of: Abbott